The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/7016467
|View full text |Cite
|
Sign up to set email alerts
|

Massive Cervicothoracic Subcutaneous Emphysema and Pneumomediastinum Developing during a Dental Hygiene Procedure

Abstract: Subcutaneous emphysema is rare during or after dental procedures (usually extractions). Here, we describe the case of a 65-year-old woman who developed massive cervicothoracic subcutaneous emphysema and pneumomediastinum during a dental hygiene procedure employing an artificial airflow. She was diagnosed based on clinical manifestations and computed tomography (CT). CT revealed massive subcutaneous emphysema extending from the superior left eyelid to the diaphragm. We describe the clinical and radiological cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The supra-hyoid spaces are contiguous with infra-hyoid spaces, notably the parapharyngeal and retropharyngeal spaces, which can lead to the mediastinal compartment. Different procedures have been associated with cervicofacial emphysema, ranging from endodental treatment to teeth extractions, even hygiene procedures [42]. Use of air syringes, or more frequently air-driven dental handpieces, which inject air at high pressure, are prominent risk factors [3].…”
Section: Discussionmentioning
confidence: 99%
“…The supra-hyoid spaces are contiguous with infra-hyoid spaces, notably the parapharyngeal and retropharyngeal spaces, which can lead to the mediastinal compartment. Different procedures have been associated with cervicofacial emphysema, ranging from endodental treatment to teeth extractions, even hygiene procedures [42]. Use of air syringes, or more frequently air-driven dental handpieces, which inject air at high pressure, are prominent risk factors [3].…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, subcutaneous emphysema and/or pneumomediastinum are benign and self-limiting 29) . These cases need observation with prophylactic antibiotics to prevent secondary infections caused by the introduced bacteria 8,16) .…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Lee et al reported only nine cases, including their own, associated with the use of air-powder abrasive devices; however, to the best of our knowledge fourteen cases of CSE due to the use of air-flow in twelve articles have been reported in the literature to date. 6,[8][9][10][11][12][13][14][15][16][17] Therefore, here we report the fifteenth case. Interestingly, all reported cases consisted of non-surgical periodontal procedures such as implant and dental cleaning procedures or non-surgical peri-implantitis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Six of the previously reported cases were associated with pnemomediastinum, no pneumothorax or airembolism were reported in any of these cases. 7,11,12,14,16,17 Only one case of implant-cleaning related emphysema progressed to mild pneumothorax. 8 We found a pneumomediastinum without pneumothorax and air-embolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation